PLA nanocomposites with antimicrobial action, based on olive fruit polyphenols and citrus fruit extracts encapsulated in Maltodextrin - Tudose, I. V.; Rosca, I.; Romanitan, C.; Ionescu, O. N.; Petrotos, K.; Zaoutsos, S.; Suchea, M. P.; Koudoumas, E. (CAS proceedings, 2021)
Research for new composite materials with antimicrobial properties suitable for food packing is a challenging subject. This report concerns fabrication of novel poly(lactic acid) (PLA) antimicrobial composite materials incorporating olive fruit polyphenols and citrus fruit extracts and encapsulated in Maltodextrin DE18, using the hot roll mill technique. Composites containing different concentrations of the active compound were produced and pressed into 1mm thick plates and their physical and antimicrobial properties were studied. The study proved that these composite materials presented antimicrobial activity against a Gram-positive bacterial strain, represented by S. aureus, and a Gram-negative bacterial strain, represented by E. coli. The antimicrobial efficiency was found increasing with the concentration of the active material and to be more effective in the Gram-positive bacterial strain.